Zespół Annette von Droste-Hülshoff – opis przypadku - Pawlak, Marta; Gotz-Więckowska, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: Annette von Droste-Hülshoff syndrome is characterized by pseudostrabismus due to macular ectopy in retinopathy of prematurity. The aim of the study is to present the case of Annette von Droste-Hülshoff syndrome. Material and methods: Fourteen years old girl was referred to the Outpatient Clinic of the Department of Ophthalmology of University of Medical Sciences in Poznan in order to attain qualification to surgical treatment of divergent strabismus of her left eye. Divergent strabismus of the left eye was diagnosed in early childhood. The girl was born in 32-nd week of twin pregnancy with a birth weight 1520 g. Her corrected vision was 1.0 for each eye with an apparent exotropia of both eyes and normal position of the head. The Hirschberg test revealed corneal reflex shifted to the nasal margin of the pupil. On eye fundus examination temporal pulling of vessels and temporal displacement of macula was noted in each eye. Kappa angle value was +8 degrees for each eye. Results: Pseudoexotropia due to temporal macular ectopy was diagnosed (in the course of suffered ROP). The girl was not qualified to surgical treatment. Conclusions: This case emphasizes fundamental importance of correct diagnosis and qualification to surgical treatment of strabismus.